Aplikasi Pupuk Bokashi Padat Berbahan Dasar Berbeda terhadap Pertumbuhan dan Produksi Tanaman Krokot (Portulaca oleracea L.) - Maria Irma Naisoko (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2021)
The purpose of this study was to see the application of solid bokashi fertilizer with different ingredients on the growth and production of purslane (Portulaca oleracea. L.). This research was conducted on 02nd March 2020, located on the agricultural land of the University of Timor. The method used in this research is a field experiment that applies a completely randomized design (CRD) consisting of 4 treatments and 4 replications so that there are 16 experimental units. The treatments tested consisted of R0: Bokashi without fertilizer (control), R1: Bokashi Fertilizer made from Chicken Excreta, R2: Bokashi Fertilizer Made from Cow Feces, R3: Bokashi Fertilizer Made from Goat Feces. The variables observed in this study were stem diameter (mm), number of tillers, spreading length (cm), fresh plant weight (grams) and plant dry weight (grams). The results showed that offering solid bokashi made from cow more significantly supported the growth and production of purslane (Portulaca oleracea. L.). Of the four (4) treatments, namely R0, R1, R2 and R3, in general the application of solid bokashi fertilizer made from cow feces (R2) significantly supported the growth and production of purslane (Portulaca oleracea. L.). In the stem diameter parameter, R2 was 0.39, the length of the spread, R2 was 8.53, the number of tillers, R2 was 2.11, plant fresh weight, R2 was 3.17, while on the plant dry weight parameter, R2 had no significant effect, which is only 0.40. It can be concluded that giving bokashi made from chicken and cow feces is very active in increasing the value of growth and production of purslane plant, because it contains nutrients needed for plant growth.